Experimental analysis of the effect of water pressure on the atomization performance of a Linear Laval nozzle and comparison with numerical analysis - Shanshan, Tang; Mohd Danial, Ibrahim; Andrew Ragai, Henry Rigit; Wei, Zhang; Chaokun, Wei (SciELO - Scientific Electronic Library Online, 2024)
Inhaling dust can lead to respiratory diseases, and dust accumulation in the workplace can pose fire and explosion hazards. Traditional dust removal nozzles require high water pressure and produce large droplet diameters. The Laval nozzle, utilizing a converging-diverging section to accelerate fluid to supersonic speeds, achieves finer droplets and a more concentrated particle size distribution. However, curved Laval nozzle is different to manufacture. To study the effect of water pressure on the atomization performance of a Linear Laval nozzle, a laser particle analyzer and a camera were used to test the droplet size and atomization angle. These results were compared with numerical analysis. The findings indicate that as the water pressure increases from 0.1 MPa to 0.5 MPa, the dropletsʼ Sauter Mean Diameter (SMD) increases almost linearly. At the same time, the spray angle tends to decrease. Both experimental and numerical analyses show the same trend. At a water pressure of 0.1 MPa, the atomization performance of the Linear Laval nozzle is optimal. Compared to traditional nozzles, the water pressure is significantly reduced, and the D(3,2) droplet diameter is notably smaller. Moreover, the atomization angle is considerably increased. The spray effect has been significantly improved